1998
DOI: 10.1128/jvi.72.2.1060-1070.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Product of the Herpes Simplex Virus Type 1 UL25 Gene Is Required for Encapsidation but Not for Cleavage of Replicated Viral DNA

Abstract: The herpes simplex virus type 1 (HSV-1) UL25 gene contains a 580-amino-acid open reading frame that codes for an essential protein. Previous studies have shown that the UL25 gene product is a virion component (M. A. Ali et al., Virology 216:278-283, 1996) involved in virus penetration and capsid assembly (C. Addison et al., Virology 138:246-259, 1984). In this study, we describe the isolation of a UL25 mutant (KUL25NS) that was constructed by insertion of an in-frame stop codon in the UL25 open reading frame a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
2
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 53 publications
7
72
2
2
Order By: Relevance
“…The phenotype of the VP26 null mutation in nucleocapsid maturation observed in this study was similar to that of the UL25 null mutation, as previously reported (7,34). The UL25 null mutation (i) had no obvious effect on cleavage of replicated HSV-1 DNA concatemers, (ii) impaired packaging of viral DNA genomes, and (iii) accumulated type A capsids and reduced type C capsid formation in the nuclei of infected cells (7,34). Interestingly, of the HSV-1 regulators for viral DNA genome packaging, this phenotype is unique to UL25.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The phenotype of the VP26 null mutation in nucleocapsid maturation observed in this study was similar to that of the UL25 null mutation, as previously reported (7,34). The UL25 null mutation (i) had no obvious effect on cleavage of replicated HSV-1 DNA concatemers, (ii) impaired packaging of viral DNA genomes, and (iii) accumulated type A capsids and reduced type C capsid formation in the nuclei of infected cells (7,34). Interestingly, of the HSV-1 regulators for viral DNA genome packaging, this phenotype is unique to UL25.…”
Section: Discussionsupporting
confidence: 90%
“…The HSV-1 terminase cleaves nascent viral concatemeric DNA into unit-length viral genomes, docks at the capsid portal vertex, and packages a cleaved progeny virus genome into the capsid (3)(4)(5). In addition, the UL25 and UL17 components of CVSCs have been reported to be required for cleavage and/or packaging of nascent HSV-1 DNA genomes (6,7).…”
mentioning
confidence: 99%
“…The capsid associated tegument complex (CATC – previously termed CCSC and CVSC), comprised of pUL17, pUL25 and pUL36 binds to the triplexes and hexons about the icosahedral five-fold vertices of mature capsids within the nucleus 16-21 . Notably, it has been observed that pUL25 is essential for retention of DNA within the nucleocapsid 22,23 . Moreover, pUL25 has also been shown to be important for genome release 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The translocation of concatenated viral DNA into procapsids and its cleavage at packaging sites is not understood. Recent studies with herpes simplex virus type 1 (HSV-1) mutants defective in UL6, UL15, UL25, UL28, UL32 or UL33 suggest that these genes are essentially involved in viral DNA cleavage and packaging, since cells infected with these mutants produce only B capsids lacking DNA (Al-Kobaisi et al 1991;Baines et al 1997;Weller 1996, 1998;McNab et al 1998;Patel et al 1996;Tengelsen et al 1993;Yu et al 1997). The respective homologues of these genes in HCMV are UL104, UL89, UL77, UL56, UL52 and UL51 (Chee et al 1990).…”
Section: Terminase Inhibitorsmentioning
confidence: 99%